Mango and diabetes - Kalra, Bharti; Gupta, Lovely; Khandelwal, Deepak; Choubey, Nishant (Journal of Social Health and Diabetes, 2018)
The mango is considered as the king of fruits. It is one of the most consumed seasonal fruits in South Asia. Most persons with diabetes and health-care providers assume that mango should be strictly avoided by persons with diabetes. However, mango is a fruit with good nutritive value, low glycemic load as well as with acceptable glycemic index. In this short review, we summarize the nutritive values of mango, as well as the ways in which mangoes can be enjoyed, in moderation, by persons with diabetes.
Keywords: Diabetes; fruits; glycemic index; mango